Besieged cities: Representations of the fear of death and illnesses in the pandemic of COVID-19 and in the cartoons of the end of the nineteenth century in Brazil - Bandeira , Élcia de Torres (Seven Editora, 2023)
The epidemics plagued Brazil in several periods of history, such as the end of the 19th century and had a large effect on Revista Ilustrada, coordinated by the Italian-Brazilian cartoonist Ângelo Agostini. The fear of illnesses and death accompanies us throughout history and generates practices and representations associated with the historical context of the time. Today, the pandemic of  the covid-19 reaps thousands of lives in Brazil and in the world, and the way we appropriate the tragic reality leads us to produce representations that slip, in many cases, to scientific denialism and contribute to the fact that many lives are still lost by discourses and practices emptied of scientific foundation. Besieged, cities face the microscopic enemy with social distancing and basic hygiene health measures, while vaccination cannot immunize the majority of the Brazilian population.  Love and empathy become lenient summing up in the void left by the absence of sufficient vaccines or specific remedy against coronavirus to date, march 20, 2021. Previously closed windows are opened to provide the sight of the other.  We will highlight in this article the relationship between feelings and their representative expressions related to the fear of death and illnesses in written and iconographic languages and seek to articulate them to the historical facts that served as a stage for its construction. Analyzing the practices and representations associated with public health and developing a comparative study between the epidemics of the late nineteenth century and the pandemic of the covid-19 becomes relevant to find realistic solutions that lead us safely to freedom, health and the enjoyment of community life. DOI:https://doi.org/10.56238/emerrelcovid19-073